Assessing the utility of mutual information stored in protein-protein interfaces to infer specific protein partners - Pontes, Camila Ferreira Thé (2021)
Tese (doutorado)—Universidade de Brasília, Instituto de Ciências Biológicas, Departamento de Biologia Celular, Programa de Pós-Graduação em Biologia Molecular, 2021.